Can Thrombelastography Predict Venous Thromboembolic Events in Patients With Severe Extremity Trauma?. Issue 6 (June 2016) - Gary, Joshua L.; Schneider, Prism S.; Galpin, Matthew; Radwan, Zayde; Munz, John W.; Achor, Timothy S.; Prasarn, Mark L.; Cotton, Bryan A.
Abstract : Objectives: An elevated maximal amplitude (mA) value with rapid thrombelastography on admission can identify general trauma patients with an increased risk of venous thromboembolic events (VTEs). We hypothesized that (1) the risk of VTE traditionally assigned to injury lies specifically in those who sustain major orthopaedic trauma and (2) an elevated admission mA value could be used to identify patients with major orthopaedic injuries at risk for VTE during initial hospital admission. Design: Retrospective. Setting: University level 1 trauma center. Patients/Participants: Consecutive trauma patients admitted to an urban level 1 trauma center between September 2009 and February 2011 who met the criteria for level 1 trauma activation and who were between 18 and 85 years of age were included in our study group. Two groups were created, one whose extremity abbreviated injury severity score was 2 or greater (ORTHO) and the other whose extremity abbreviated injury severity score was <2 (non-ORTHO). Main Outcome Measurements: Pulmonary emboli were confirmed by computed tomography angiography, and deep vein thromboses were confirmed by venous duplex. Univariate analyses were conducted and followed by purposeful regression analysis. Results: Of note, 1818 patients met the inclusion criteria (310 ORTHO and 1508 non-ORTHO). Despite more hypocoagulable r-TEG values on arrival (alpha angle 71 vs. 73 and mA 62 vs. 64, both P < 0.05), ORTHO patients had higher rates of VTE (6.5% vs. 2.7%, P < 0.001). Stepwise regression generated 4 values to predict development of VTE (age, male gender, white race, and ORTHO). After controlling for these variables, admission mA values ≥65 (odds ratio 3.66) and ≥72 (odds ratio 6.70) were independent predictors of VTEs during hospitalization. Conclusions: Admission rapid thrombelastography mA values can identify patients with major orthopaedic trauma injuries who present with an increased risk of in-hospital deep vein thromboses and pulmonary embolism with a 3.6-fold and 6.7-fold increased risk for mA values ≥65 and ≥72, respectively. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.